KEKUATAN KOLABORASI MAHASISWA DAN MASYARAKAT DALAM PENGUATAN BUDAYA PEDULI LINGKUNGAN KOTA - Jahroni Jahroni; Panji Prima Rosuli; Didit Darmawan; Samsul Arifin; Arif Rachman Putra (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to foster a spirit of mutual cooperation, strengthen collaboration between higher education institutions and government agencies, and increase environmental awareness among students and the community. In addition, the program is intended to create a cleaner and better-maintained Afvoer Kemambang area. The methods used include a participatory approach through Participatory Action Research (PAR), field actions such as waste clean-up activities, community education, and activity documentation. The results show positive impacts, including improved environmental cleanliness, increased public awareness in maintaining drainage systems, and the strengthening of students’ social values and environmental responsib ility. Furthermore, a constructive partnership was established between Universitas Sunan Giri Surabaya and the Environmental Agency (DLH) of East Java. This activity demonstrates that multi-stakeholder synergy through collaboration and environmental education is effective in enhancing community participation and addressing urban environmental cleanliness issues.